The Development Of A Candidate Tuberculosis Dna Vaccine Expressing MtbS.4 And Ag858 of Mycobacterium Tuberculosis - Azlan, Maryam (2007)
Tuberculosis (TB) is still one of the major health problems worldwide. The only TB vaccine currently available is an attenuated strain of Mycobacterium bovis, bacille ealmette Guerin (BeG). However, the efficacy of BeG vaccine continues to be debated. Therefore, a more effective vaccine against TB is urgently needed. DNA vaccination is a new approach to the control of infectious agents. In this study, a DNA vaccine encoding the candidate TB antigens Mtb8.4 and Ag85B was developed using assembly peR. Balb/c mice were immunized intramuscularly with 50 JAg of the DNA vaccine, pNMN023, containing the two antigens. in each hindleg. Reactivity against the Ag85B peptides, P1 and P3 as well as Mtb8.4 showed a consistent Th1 type of immune response by virtue of the increased expression of IL-2, IFN-y and IgG2a. Splenocytes from immunized mice were also found to proliferate more aggressively when stimulated with the antigens compared to the vector alone. In order to improve the vaccine efficacy, a preliminary prime-boost approach was used. Priming with pNMN023 and boosting with recombinant BeG (rBeG) in Balb/c mice was carried out. Flow cytometric intracellular cytokine analyses of splenocytes from mice immunized with the DNA-rBeG prime-boost regime showed that both CD4+ and CD8+ T cells showed an increase in IL-2 and IFN-y production following stimulation with either antigens at significantly higher levels than those immunized with rBeG-DNA prime-boost. In conclusion, the data obtained from this study suggest that DNA vaccination in combination with the prime-boost approach provide a potential strategy for developing a candidate vaccine against TB.